FORMATION AND MECHANISMS FOR STATE ECONOMIC POLICY IMPLEMENTATION AT REGIONAL LEVEL - Pastuh K.V. (Pressing Problems of Public Administration, 2015)
The state economic policy formation and mechanisms of its implementation at the regional level have been researched. The paper investigates the stages of state economic policy formation at the regional level. The regulatory, organizational, and economic mechanisms of the state economic policy implementation at the regional level have been considered.